Black Scholars’ Burden: An examination of life and career experiences of African-American faculty at a PWI - Robinson, Michelle (My University, 2020)
In this narrative study, the researcher examined African-American faculty members’ experiences in their efforts to earn and sustain roles as university faculty members. Previous researchers indicated that African-American faculty members are underrepresented at a southeastern U.S. university research institution, holding fewer than six percent of the faculty positions compared to sixty percent of their White counterparts (Lite Report, 2019). Critical Race Theory and Black Feminist Thought were the theoretical frameworks for this qualitative narrative inquiry. Seidman’s (2006) three-step interview model served as a guide for interviews with six African-American faculty members at a predominantly White institution (PWIs). Four major themes emerged from the data analysis: burden of Blackness, politics of isolation and omission, paradox of diversity at a PWI, and extended roles and responsibilities of African-American faculty in PWIs. Participants used grit augmented by family encouragement to overcome barriers, including racial stereotypes and extended faculty roles. The participants in this study shared valuable, diverse instructional and advising perspectives that may benefit all faculty in higher learning institutions. Additionally, outside of their research and teaching responsibilities, the participants devoted additional time and effort to support, mentor, and serve as role models for underrepresented student populations at their university. Keywords: African-American Faculty, career experiences, PWI, Burden, underrespresented, minority
ABSTRACT I -- LIST OF TABLES VII -- ACKNOWLEDGEMENTS VIII -- I. INTRODUCTION 1 -- Overview 1 -- Problem Statement 4 -- Purpose Statement 4 -- Research Questions 5 -- Significance of the Study 5 -- Theoretical Framework 7 -- Summary of the Methodology 8 -- Limitations 9 -- Definition of Key Terms 10 -- Chapter Summary 11 -- II. REVIEW OF LITERATURE 12 -- Theoretical Frameworks 16 -- Critical Race Theory 16 -- Black Feminist Thought 18 -- Research Method 22 -- African-American Females Faculty in Higher Education 22 -- African-American Males Faculty in Higher Education 24 -- Career Experiences of African-American Faculty 26 -- Barriers of African-American Faculty at PWIs 27 -- Critical Mass 30 -- Marginalization 31 -- Strategies Used by African-American Faculty 33 -- Self-Identity of African-American Faculty 34 -- Mentoring 35 -- Importance of African-American Faculty 38 -- Organizational Culture and Policies 43 -- The Recruitment of African-American Faculty 44 -- The Retention of African-American Faculty 46 -- Diversity in Higher Education 48 -- Development of Diversity Initiatives 50 -- Chapter Summary 51 -- III. METHODOLOGY 53 -- Introduction 53 -- Researcher Design and Rationale 54 -- Research Setting 55 -- Participant Selection 57 -- Data Collection Procedures 58 -- Interviews 59 -- Memos 61 -- Data Analysis Procedures 61 -- Validity 63 -- Researcher Bias 63 -- Reactivity 64 -- Intensive, Long-Term Involvement 64 -- Transferability 64 -- Respondent Validation/Member Checking 65 -- Searching for Discrepant Evidence and Negative Cases 65 -- Triangulation 65 -- Ethical Issues 66 -- Chapter Summary 68 -- IV. RESULTS 69 -- Narratives of African-African Faculty Members 69 -- Participant Narratives 72 -- Faith 72 -- Michael 77 -- James 83 -- Dee 92 -- Joe 99 -- Christian 107 -- Chapter Summary 117 -- V. DISCUSSION OF THEMES 118 -- Data Analysis 118 -- Themes 121 -- Theme 1: Burden of Blackness 121 -- Theme 2: Politics of Isolation and Omission 134 -- Theme 3: Paradox of Diversity at a PWI 142 -- Theme 4: Extended Roles and Responsibilities of African-American Faculty in PWIs 151 -- Chapter Summary 158 -- VI. DISCUSSION AND CONCLUSION 160 -- Research Questions: Final Discussions Summary 162 -- Research Question 1 162 -- Research Question 2 165 -- Research Question 3 172 -- Final Discussion 175 -- Research Findings 176 -- Discussion 178 -- Limitations and Implications for Further Study 181 -- Policy Implications 183 -- Recommendations for Future Research 184 -- Final Conclusions 186 -- Final Note 189 -- Recommendations to a Young African-American Faculty Member in a PWI 191 -- REFERENCES 193 -- APPENDIX A: PARTICIPANT FLYER 226 -- APPENDIX B: PARTICIPANT INVITATION LETTER 228 -- APPENDIX C: PRELIMINARY PARTICIPANT PROFILE FORM 231 -- APPENDIX D: RESEARCH STATEMENT (CONSENT TO PARTICIPATE) 233 -- APPENDIX E: INTERVIEW QUESTIONS 236 -- APPENDIX F: IRB PROTOCOL EXEMPTION REPORT 243 -- APPENDIX G: RULES FOR THE STUDY 246
Keywords: Dissertations, Academic--United States; African Americans; Universities and colleges--Faculty; Minorities--Employment; Minorities--Education (Higher)